2001
DOI: 10.1891/1521-0987.3.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Looking Beyond Caseload Numbers for Long-Term Home-Care Case Managers

Abstract: Determining the best use of case managers’ time is difficult both because of the great variability in the factors and the lack of outcome studies. In place of the outcome studies, the responses to focus group questions of 89 experienced case managers from across Canada were used to indicate a value for case management functions in the areas of direct care, indirect care management, and program management. The case managers identified greater value for direct care with clients and families who are new to home c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…2007), but rely on a supportive healthcare system. Case managers have been reported to be frustrated by the lack of agency and community policies and resources to allow case managers to properly support people in their homes (Diem et al. 2001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2007), but rely on a supportive healthcare system. Case managers have been reported to be frustrated by the lack of agency and community policies and resources to allow case managers to properly support people in their homes (Diem et al. 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Certainly, smaller caseloads in community case management for frail older people reduce hospital-related healthcare expenditure (Leung et al 2004, Onder et al 2007, but rely on a supportive healthcare system. Case managers have been reported to be frustrated by the lack of agency and community policies and resources to allow case managers to properly support people in their homes (Diem et al 2001). The efficient and effective use of a scarce resource, case managers' time, signals the need for case managers acting as advocates and catalysts for systems level change to create more appropriate responses for clients (Case Management Society of Australia 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have indicated that outcome evaluation is also an important case management function [ 11 – 13 ], but there are debates on whether it is an independent function or it overlaps or is part of the monitoring and review function in individual case managers’ practice [ 13 ]. While some empirical studies (examining frequency ratings of different case management activities) have reported that in their practice case managers perform outcome evaluation activities less frequently than the other case management activities [ 5 , 8 , 9 ], some empirical [ 13 ] and commentary studies [ 12 , 14 ] have revealed that case managers do not perform outcome evaluation adequately because they lack time, knowledge of goals/outcomes and goal setting, capacities, and organisational support.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a paucity of studies based in community aged care that focus on how case managers allocate time to the primary case management functions, or how frequently they undertake those functions and specific case management activities. Some studies have reported that case managers spend considerable time on care coordination as well as more time on initial assessment compared with monitoring and review [ 14 16 ]. However, these studies examined different case management function domains (such as direct care, indirect case management, and program management), and/or were based in other care settings but not specifically in community aged care.…”
Section: Introductionmentioning
confidence: 99%